OCEANS 2007 - Europe 2007
DOI: 10.1109/oceanse.2007.4302236
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Propagation-delay-tolerant MAC Protocol for Underwater Acoustic Sensor Networks

Abstract: To support the retrieval of accurate and up-to-date information from beneath the world's oceans, it is desirable to deploy underwater sensor networks. However, since radio frequencies (RF) do not propagate well underwater, acoustic channels are employed to support long-distance and low-power communication in underwater sensor networks even though acoustic signals suffer from long propagation delay and have very limited bandwidth. In this paper, we first show the limitation of conventional MAC protocols in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 19 publications
0
33
0
1
Order By: Relevance
“…In real networks, there are other factors, time delays [16], that would affect the global detection, including the transmission delay [17] and the propagation delay [18]. We only consider the single data packet routing, a node issued a certificate, after node path forwarding until the destination, if each node has to transmit delay, and then the total number of the transmission delays of this path is the number of the path nodes.…”
Section: Detection Probabilitymentioning
confidence: 99%
“…In real networks, there are other factors, time delays [16], that would affect the global detection, including the transmission delay [17] and the propagation delay [18]. We only consider the single data packet routing, a node issued a certificate, after node path forwarding until the destination, if each node has to transmit delay, and then the total number of the transmission delays of this path is the number of the path nodes.…”
Section: Detection Probabilitymentioning
confidence: 99%
“…To solve such problems, Guo et al [3][4] suggested a protocol that is strong despite a long propagation delay. This protocol transformed the existing handshaking mechanism.…”
Section: Related Workmentioning
confidence: 99%
“…These are schedule based and non-schedule based protocols [8]. The existing non-schedule based protocols are like ALOHA [9], [10] and CSMA/CA [11]. Their implementation is simple, but they suffer from increased collisions at low data rates.…”
Section: Introductionmentioning
confidence: 99%